Group B Streptococci Screening Before Repeat Cesarean Delivery: A Cost-Effectiveness Analysis. Issue 1 (January 2017) - Albright, Catherine M.; MacGregor, Caitlin; Sutton, Desmond; Theva, Meena; Hughes, Brenna L.; Werner, Erika F.
Abstract : OBJECTIVE: To estimate the cost-effectiveness of universal group B streptococci (GBS) screening in women with a singleton pregnancy planning a repeat cesarean delivery. METHODS: We conducted a decision analysis from a health care perspective to compare the cost-effectiveness of GBS screening for women planning a repeat cesarean delivery. With universal screening, all GBS-positive women who labored before a scheduled cesarean delivery received antibiotic prophylaxis. With no screening, women who presented in labor received antibiotics based on risk-based criteria. Neonates born to women colonized with GBS were at risk for early-onset GBS disease, disability, and death. We assumed a GBS prevalence of 25%, that 26.6% of women labored between 35 weeks of gestation and their scheduled time for cesarean delivery, and that 3.3% who planned a repeat cesarean delivery instead delivered vaginally. The primary outcome was cost per neonatal quality-adjusted life-year gained, with a cost-effectiveness threshold of 100, 000 per quality-adjusted life-year. Neonatal quality of life was assessed using five health states (healthy, mild, moderate, or severe disability, and death) with a life expectancy of 79 years for healthy neonates. One-way sensitivity and Monte Carlo analyses were used to evaluate the results. RESULTS: In the base case, universal GBS screening in women planning a repeat cesarean delivery was not cost-effective compared with no screening, costing 114, 445 per neonatal quality-adjusted life-year gained. The cost to prevent an adverse outcome from GBS exceeded 400, 000. If greater than 28% of women were GBS-positive, greater than 29% labored before their scheduled delivery, or greater than 10% delivered vaginally, universal screening became cost effective. CONCLUSION: Universal GBS screening in women with a singleton pregnancy planning a repeat cesarean delivery may not be cost-effective in all populations. However, in populations with a high GBS prevalence, women at high risk of laboring before their scheduled cesarean delivery, or women who may ultimately opt for a vaginal delivery, GBS screening may be cost effective. Abstract : Universal group B streptococci screening in women with a singleton pregnancy intending to have a repeat cesarean delivery may not be cost-effective in all populations.